Association of Perfluoroalkyl Substance with Lung Function in the US Population - Brenna C. Heinle; Tim N. Crawford; Sara J. Paton; Naila Khalil (Ohio Journal of Public Health, 2019)
Background/Aim: Perfluoroalkyl substances (PFASs) are chemical compounds used in consumer products and are linked with increases in cholesterol, thyroid disease, and pregnancy-induced hypertension. However, their association with lung function is not completely understood. Methods: Cross-sectional 2011-2012 US population data from the National Health and Nutrition Examination Survey (NHANES) were analyzed (n = 1450, aged 12 to 79 years, 50.5% females). Serum concentrations of 4 PFASs, perfluoronon-anoic acid (PFNA), perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), and perfluorohexane sulfonic acid (PFHxS), were assessed using mass spectrometry and categorized into quartiles. Lung function was measured by spirome-try as forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and the ratio of FEV1/FVC (%). Survey weighted sex stratified adjusted linear regression analysis was used to predict lung function with PFASs quartiles. Results: In males, compared to females, all 4 PFASs serum concentrations and lung function indices were higher, except FEV1/FVC (%) which was lower than females. No association of any PFAS with decrease in lung function was seen in multivariable-adjusted models in both males and females. Conclusion: In this exploratory analysis, PFAS exposure was not associated with lung function. PFAS contamina-tion has been ongoing for many years across the US and Ohio, and cleanup efforts are now underway. The association between PFAS exposure and lung function needs further exploration in longitudinal studies.
Keywords: Perfluoroalkyl substances; PFAS; NHANES; Lung function